Immunohistochemical Detection and Localization of Somatostatin Receptor Subtypes in Prostate Tissue from Patients with Bladder Outlet Obstruction - Rodolfo Montironi; Liang Cheng; Roberta Mazzucchelli; Doriana Morichetti; Daniela Stramazzotti; Alfredo Santinelli; Gianluca Moroncini; Andrea B. Galosi; Giovanni Muzzonigro; Giancarlo Comeri; Jon Lovisolo; Sergio Cosciani-Cunico; et al. (Cellular Oncology)
Background and Aim of the Study: Scant information on the cellular distribution of the five somatostatin receptor (SSTR) subtypes in the normal prostate and in neoplasms of the prostate has been reported in very few studies in which techniques, such as in situ hybridization histochemistry, autoradiography, and more recently immunohistochemistry, have been applied. The aim of the study was to examine immunohistochemically the distribution and localization of these 5 subtypes in the various tissue components in normal prostate.